Inflammation and thrombosis in diabetes - Hess, Katharina; Grant, Peter J. (Thrombosis and Haemostasis, 2011)
Patients with diabetes mellitus are at increased risk of cardiovascular morbidity and mortality. Atherothrombosis, defined as atherosclerotic lesion disruption with superimposed thrombus formation, is the most common cause of death among these patients. Following plaque rupture, adherence of platelets is followed by local activation of coagulation, the formation of a cross-linked fibrin clot and the development of an occlusive platelet rich fibrin mesh. Patients with diabetes exhibit a thrombotic risk clustering which is composed of hyper-reactive platelets, up regulation of pro-thrombotic markers and suppression of fibrinolysis. These changes are mainly mediated by the presence of insulin resistance and dysglycaemia and an increased inflammatory state which directly affects platelet function, coagulation factors and clot structure. This prothrombotic state is related to increased cardiovascular risk and may account for the reduced response to antithrombotic therapeutic approaches, underpinning the need for adequate antithrombotic therapy in patients with diabetes to reduce their cardiovascular mortality.
Keywords: Diabetes mellitus; inflammation; thrombosis; cardiovascular disease